Hibiscus sabdariffa L no tratamento para obesidade: uma revisão integrativa - CAVALCANTE , Mariana (2024)
Plant species and their derivative preparations have been popularly used for the treatment of obesity and weight loss. The use of Hibiscus sabdariffa has aroused interest, given the growing consumption by the population for this purpose. Obesity is a disease characterized by the excessive accumulation of fat in the body, thus becoming a risk for the development of chronic and disabling diseases. For this reason, new alternatives have been sought for the treatment of obesity. Therefore, the objective of this work was to carry out an integrative review of the literature on the evidence of the use of Hibiscus sabdariffa L in the treatment of obese rats. This is an integrative review of the literature, carried out in 6 stages which consisted of: 1) identification of the theme; 2) formulation of the guiding question; 3) literature search; 4) categorization of studies found; 5) analysis of included studies and 6) interpretation of results. The search for articles was carried out through the VHL, SCIELO and PubMed databases, using the health descriptors (DECS), “Hibiscus sabdariffa L”, “medicinal plants”, “obesity”, “clinical studies”, “studies in vivo'' interconnected by the Boolean operators “AND” and “OR”. Initially, 11 articles were found, which after applying the inclusion and exclusion criteria, resulted in two articles analyzed. The results obtained suggest that Hibiscus sabdariffa L can reduce caloric intake, body weight and body fat, increasing functional capacity in obese rats. Hibiscus sabdariffa L is rich in polyphenols, such as anthocyanins, flavonoids and phenolic acids, these metabolites help prevent hyperlipidemia, through the inhibition of lipogenesis, while promoting hepatic lipid clearance. Additionally, other compounds such as gallic acid derivatives, chlorogenic acid, caffeic acid, quercetin, and tiliroside have demonstrated efficacy in reducing obesity and metabolic disorders. Given these results, it is concluded that Hibiscus sabdariffa L can be a therapeutic alternative in weight control, as it is observed that this plant is capable of helping the weight loss process